Cross-Cultural Adaptation and Validation to Chilean Youth People of Brief Resilience Scale (BRS) - Hidalgo-Rasmussen, Carlos Alejandro; Chávez-Flores, Yolanda Viridiana; Rojas María, Jaqueline; Vilugrón, Fabiola (Anales de Psicología / Annals of Psychology, 2021)
The study of resilience as recovery from stress has been extended, and it is necessary to account for the development and psychometric properties of the scales that allow it to be used. The aim was to report on the cross-cultural adaptation process and psychometric properties of the Brief Resilience Scale (BRS) in young Chilean population. In 2016, three translators, and 1,237 students between 18 and 24 years old from a university in the Fifth Region of Chile participated. Linguistic and conceptual equivalence was achieved after carried out a double translation, back-translation and cognitive interviews with the target population. Difficulties were observed in item 2. From the Exploratory Factor Analysis, two factors emerged. In the Confirmatory Factorial Analysis, the fit indexes were suitable: χ2 = 9.256(6), p = .160; CFI = .995; TLI = .988; RMSEA = .035 CI 90% [.000, .076]. Total omega was .81. The stability per item was moderate; and high for the total score. Means were generally lower in women than in men but similar among age groups. It has evidence for concurrent and convergent validity. The BRS Chilean version might be useful for measuring resilience in young Chileans.